2021
DOI: 10.7759/cureus.15602
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Disorders (SUD) and Suicidal Behaviors in Adolescents: Insights From Cross-Sectional Inpatient Study

Abstract: Basith et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…Overall, individuals in this cohort were highly vulnerable, with most reporting serious MD as well as high material and social deprivation, nearly half had chronic physical illnesses, about a third were high ED users with no usual physician, and many did not receive any psychosocial interventions from community healthcare centers. As in previous studies [ 42 , 43 ], findings show that patients hospitalized for suicide attempts and MD-SRD had a higher risk of early readmission, particularly among young patients. According to a recent study [ 44 ], the risk of rehospitalization for suicidal behaviors is higher within the first month after discharge, mainly among patients with SRD, or depressive and anxious disorders.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, individuals in this cohort were highly vulnerable, with most reporting serious MD as well as high material and social deprivation, nearly half had chronic physical illnesses, about a third were high ED users with no usual physician, and many did not receive any psychosocial interventions from community healthcare centers. As in previous studies [ 42 , 43 ], findings show that patients hospitalized for suicide attempts and MD-SRD had a higher risk of early readmission, particularly among young patients. According to a recent study [ 44 ], the risk of rehospitalization for suicidal behaviors is higher within the first month after discharge, mainly among patients with SRD, or depressive and anxious disorders.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, this issue will bring more challenges for girl consumers; female consumers receive less treatment and care because of different reasons, such as social stigma and fear of ostracization (2,7). Studies indicated that among the identi ed high-risk behaviors, uncontrolled sexual behavior, suicide, and violence are among the most serious high-risk health-associated behaviors among adolescents with substance use disorder (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…4 Drug use disorders severely affect children and adolescents' physical and mental health. 5 The scientific literature underscores the widespread prevalence of psychotropic substance use among adolescents globally. A study performed in Poland showed that 10.8% of respondents aged 13 to 17 had consumed psychotropic drugs, such as cannabis, cocaine, or heroin, at least once.…”
mentioning
confidence: 99%